Gastric secretion and its facilitation as related to gastric mucosal histamine - Johansson, Irene (1972)
1. In conscious rats provided with Pavlov or Heidenhain pouches the acid and pepsin responses to vagal stimulation, or infusions of gastrin, histamine, methacholine, and to various combinations of these stimulants have been established. The concomitant mobilization and increased formation of gastric mucosal histamine have also been examined. 2. Histamine evoked graded acid responses in the Pavlov and Heidenhain pouches. The innervated pouch was more sensitive to histamine than the denervated. Stimulation of pepsin secretion was apparent only in the Heidenhain pouch. 3. The acid response to vagal stimulation evoked by 2-deoxy-D-glucose was facilitated by infusion of histamine, but not that of pepsin, the secretion of which was depressed. 4. Acid secretion in response to graded infusion of methacholine was enhanced by background infusions of histamine in subthreshold, sub-maximal and maximal dosages. 5. The acid response to vagal stimulation was enhanced by a background infusion of gastrin, but not that of pepsin, the secretion of which was depressed. 6. A background infusion of a large dose of histamine depressed the maximal acid response to gastrin in both types of pouches. 7. Administration of histamine restrained the accelerating effect of gastrin on histidine decarboxylase activity, probably by a feed-back coupling. 8. The increase in gastric mucosal histamine, as reflected in its urinary excretion, in response to gastrin infusion was enhanced by vagal stimulation. 9. The amounts of histamine that can be mobilized and newly formed in the gastric mucosa have been evaluated and found to be fully adequate for efficient stimulation of the parietal cell.